The Impact and Evolution of Group Diversity in Online Open Collaboration - Ren, Yuqing; Chen, Jilin; Riedl, John (Management Science, 2016)
Online open collaboration efforts, such as Wikipedia articles and open source software development, often involve a large crowd with diverse experiences and interests. Diversity, on the one hand, facilitates the access to and integration of a wide variety of information; on the other hand, it may cause conflict and hurt group performance. Although diversity’s effects have been the subject of many studies in offline work groups (with the results remaining inconclusive), its effects in online self-organizing groups are underexplored. In this paper, we examine 648 WikiProjects to understand (1) how tenure disparity and interest variety affect group productivity and member withdrawal and (2) how the two types of diversity evolve over time. Our results show a curvilinear effect of tenure disparity, which increases productivity and decreases member withdrawal, up to a point. Beyond that point, productivity slightly decreases, and members are more likely to withdraw. In comparison, our results show a positive effect of interest variety on productivity and no significant effects on withdrawal. We also find that, over a project’s life cycle, tenure disparity decreases and interest variety increases, with both converging toward the level that is optimal for group performance. Overall, our study highlights the importance of having diverse experiences and perspectives in online open collaboration and the power of self-organizing that helps groups evolve toward their high-performing zones. It also has practical implications on the design of collaboration tools and new forms of organizing work in traditional organizations. This paper was accepted by Sandra Slaughter, information systems.